PENGARUH PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR IPA SISWA KELAS IV DI SDN GANDASARI 1 KOTA TANGERANG - Netri; Candra Puspita Rini; Arry Patriasurya Azhar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of the scientific approach on the learning outcomes of fourth-grade students at Gandasari 1 Elementary School, Tangerang City. The research approach used was a quasi-experimental with a pretest-posttest control group design. The research sample consisted of 59 students, with 29 students in the experimental class and 30 students in the control class. The results showed that the application of the scientific approach had a significant positive impact on improving student learning outcomes. Descriptive statistical analysis showed a significant increase in average scores from pretest to posttest, as well as a strong and positive relationship between initial abilities and student learning outcomes. The test of mean differences using a paired t-test t count 7.208 > t table 2.048 statistically proved that the difference between pretest and posttest scores was significant. The findings of the scientific approach in learning that improve learning outcomes in developing student competencies in science learning. The results of this study can be a reference for teachers and schools in designing innovative and student-centered learning strategies, especially in science subjects, to optimize the achievement of science learning at the elementary school level. Keywords: Scientific Approach, to Science Learning Outcomes, in Elementary Schools